Comportamento animal e distribuição espacial das fezes em sistemas integrados de produção de leite - Mello, Andréia Cristina Tavares de (2014)
In high temperatures conditions as Brazilian Midwest, the use of trees for reduce the heat stress in dairy cattle can be determinant of productive, reproductive and healthy efficiencies. The aim was evaluated the heifers behaviour in integrated systems of production at Mato Grosso, Brazil. It was evaluated a group of 24 breed heifers with 350 kg in three periods of year. The grass used was piatã grass in three shade levels: full sun, shade by side and intensive shade, using Eucalyptus with 10 to 12 m of height. The animal behaviour was evaluated in each 15 minutes, between 8:30 am to 16:00pm. The shade availability changed the animal behaviour, mainly about grazing in the hottest hours of day and, in the grazing in the periods of year. The heifers have preferential times during the day to graze. The animals that have shade areas available looking for theirs grazing activities in the hottest hours of day during rainy, transition and dry station.